Pengembangan Model Supervisi Akademik pada Sekolah Menengah Kejuruan di Kota Semarang - Andi Maulana; Turahmat Turahmat; Leli Nisfi Setiana; Ulil Albab (IKIP PGRI Bojonegoro, 2026)
ABSTRACT The development of effective academic supervision is essential to improve the quality of learning in Vocational High Schools (SMK), particularly in Semarang City, which has dynamic vocational education demands. This community service activity aimed to develop a systematic, reflective, and technology-based academic supervision model to enhance teachers’ professionalism and performance. The implementation method employed a participatory developmental approach, including needs assessment, model design, training, limited implementation, and evaluation stages. The results indicated improvements in supervision planning, classroom observation, reflective feedback, and follow-up actions. Furthermore, there was a significant increase in teachers’ pedagogical and professional competencies after the model implementation. Teachers’ responses to the developed model were positive, particularly regarding reflective dialogue and structured documentation systems. Although challenges such as time constraints and digital literacy were identified, the academic supervision model proved practical and sustainable. Therefore, this developed supervision model contributes to improving instructional quality and teacher professionalism in vocational high schools in Semarang City. Keywords: Academic Supervision, Teacher Professionalism, Teacher Performance, Vocational High School, Community Service. ABSTRAK Pengembangan supervisi akademik yang efektif menjadi kebutuhan mendesak dalam meningkatkan mutu pembelajaran di Sekolah Menengah Kejuruan (SMK), khususnya di Kota Semarang yang memiliki dinamika pendidikan vokasi yang tinggi. Kegiatan pengabdian ini bertujuan untuk mengembangkan model supervisi akademik yang sistematis, reflektif, dan berbasis teknologi guna meningkatkan profesionalisme dan kinerja guru. Metode pelaksanaan menggunakan pendekatan partisipatif berbasis pengembangan model melalui tahapan analisis kebutuhan, perancangan model, pelatihan, implementasi terbatas, serta evaluasi. Hasil kegiatan menunjukkan adanya peningkatan pada kualitas perencanaan supervisi, observasi kelas, umpan balik reflektif, dan tindak lanjut pembinaan. Selain itu, terjadi peningkatan signifikan pada kompetensi pedagogik dan profesional guru setelah penerapan model supervisi. Respon guru terhadap model yang dikembangkan berada pada kategori positif, terutama pada aspek dialog reflektif dan sistem dokumentasi yang lebih terstruktur. Meskipun terdapat hambatan seperti keterbatasan waktu dan literasi digital, model supervisi akademik ini terbukti aplikatif dan berpotensi diterapkan secara berkelanjutan. Dengan demikian, pengembangan model supervisi akademik ini berkontribusi terhadap peningkatan mutu pembelajaran dan profesionalisme guru di SMK Kota Semarang. Kata kunci: Supervisi akademik, profesionalisme guru, kinerja guru, SMK, pengabdian masyarakat